2021
DOI: 10.1108/md-05-2020-0650
|View full text |Cite
|
Sign up to set email alerts
|

The chief financial officer (CFO) profile and R&D investment intensity: evidence from listed European companies

Abstract: PurposeThis study aims to investigate whether the characteristics of the chief financial officer (CFO) have an impact on the intensity of the corporate research and development (R&D) investment.Design/methodology/approachBased on hand-collected data for the CFOs of a sample of the largest European listed companies for the period 2013–2016, this study uses regression analyses to test empirically the association of CFO education, CFO gender and CFO age with R&D investment intensity.FindingsThe presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 84 publications
2
5
1
Order By: Relevance
“…Datta and Iskandar-Datta (2014) found that "strategic" CFOs with an elite MBA (generalist) degree consistently command a compensation premium compared with non-MBA CFOs, even from an elite institution. Ginesti et al (2021) research also supports that CFOs with MBA degrees have a positive relationship with the intensity of R&D investment. This finding implies that CFOs with MBA degrees from reputable universities have advantage over those without an MBA.…”
Section: Introductionsupporting
confidence: 54%
“…Datta and Iskandar-Datta (2014) found that "strategic" CFOs with an elite MBA (generalist) degree consistently command a compensation premium compared with non-MBA CFOs, even from an elite institution. Ginesti et al (2021) research also supports that CFOs with MBA degrees have a positive relationship with the intensity of R&D investment. This finding implies that CFOs with MBA degrees from reputable universities have advantage over those without an MBA.…”
Section: Introductionsupporting
confidence: 54%
“…The presumption is that CFO with high education will have broader insight to strengthen the company's performance, conduct supervision, and predict profits correctly. The research results by Ginesti et al [32] also found that CFO with a high educational background is more likely to give more resources for company activities such as company research and development. Moreover, according to Papadakis [33], leaders who have high education can strengthen the company's performance and affect decision-making.…”
Section: Cfo Characteristics Relationship With Audit Committee Characteristics and Real Earnings Managementmentioning
confidence: 94%
“…It appears that the primary interest of research lies in distinguishing between family and nonfamily accountants rather than being explicit about what roles accountants actually play in family firms. Here, the field might be missing the opportunity to move beyond the dichotomy adopted by family business research and instead rely on the research in the accounting domain acknowledging the different roles accountants might play in organizations vis-à-vis accounting and organizational outcomes (e.g., Ge et al, 2011;Ginesti et al, 2021). Nonetheless, implicitly, the reviewed literature alludes to a number of roles that the accountant plays in these family firms.…”
Section: An Accountant's Role In Family Firms and Research Agendamentioning
confidence: 99%